The Influence of Perceived Usefulness, Perceived Convenience and Perceived Efficiency On The Use of E-Filing For Individual Taxpayer at KPP Pratama Bulukumba - Nurul Hinayah; Agusdiwana Suarni; Wahyuni Wahyuni (Jurnal Riset Perpajakan: Amnesty, 2022)
Research data obtained from questionnaires (primary). The results of the analysis were carried out with multiple linear regression. These results indicate that the perceived usefulness variable with a significance value of 0,014 < 0,05 and t_count is greater than t_table. that is 2,517 > 1,984. From these results, it can be seen that the perceived usefulness variable has a positive and significant effect on the use of E-Filing, the perceived convenience variable shows a significance value of 0,004 < 0,05 and t_count is greater than t_table. that is 2,979 > 1,984. From these results, it can be seen that the perceived convenience variable has a positive and significant effect on the use of E-Filing and the efficient perception variable shows a significance value of 0,004 < 0,05 and t_count is greater than t_table. ie 2,918 > 1,984. From these results it can be seen that the efficient perception variable has a positive and significant effect on the use of E-Filing.